Correcting 'Beyond the Cycle" : Accounting for Asset Prices in Structural Fiscal Balances - Liu, Estelle (IMF Working Papers; Working Paper ;, 2015)
This paper outlines an operational approach for incorporating the impact of asset price cycles in the calculation of structural fiscal balances (SFBs). The global financial crisis demonstrated that movements in asset prices can have an important fiscal impact. Failing to account for the fiscal impact of asset price cycles can encourage a pro-cyclical policy stance if temporarily high revenues are passed through into expenditures. In addition, over-estimating the SFB may lead to inadequate fiscal buffers when cyclical revenues eventually dissipate. The paper proposes an empirical approach to correct for asset prices and provides illustrative country results for selected OECD countries. We find that asset price cycles are imperfectly synchronized with the business cycle and are quantitatively significant with an average pre-crisis fiscal impact ranging from about 1\2 to 2 percent of GDP in the sample. For a number of countries, the pre-crisis fiscal impact of high asset prices was larger at about 4 percent of GDP.